PENGARUH TEKNIK THINK TALK WRITE (TTW) TERHADAP KETERAMPILAN MENULIS KARANGAN ARGUMENTASI SISWA KELAS X SMA NEGERI 8 PADANG - Afriani, Yelsa; Basri, Irfani; Emidar, Emidar (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT This research is aimed to describe the influence Think Talk Write technique the of argumentation essay writing skill of student class X SMA Negeri 8 Padang. The type of this research is quantitative research done using experimental design. The results of this research are three: (1) argumentation essay writing skills before using Think Talk Write technique of student class X SMA Negeri 8 Padang are in qualifying Enough (C) with an average value of 62,72, (2) argumentation essay writing skills after using Think Talk Write technique of student class X SMA Negeri 8 Padang are in qualification Good (B) with an average value of 77,96, and (3) argumentation essay writing skills of student class X SMA Negeri 8    Padang after using Think Talk Write technique better than before using Think Talk Write technique.      Kata Kunci: pengaruh, teknik think talk write, karangan argumentasi